La inteligencia emocional en la educación física de primaria y secundaria: una revisión sistemática - Rivas, Johan; Álvarez, Juan José; Sandoval-Obando, Eduardo (Retos, 2025)
Emotional intelligence is a key factor for the social and mental well-being of students, as it allows them to perceive, understand, and regulate their emotions. In the field of Physical Education, various studies indicate that it can be considered a skill that contributes to achieving more significant learning in the classroom, as teachers can positively reinforce students' emotions through their generative behaviors. Additionally, physical activity and sports are effective tools for improving emotional balance and the physical and mental well-being of students, demonstrating the close relationship between both aspects. The objective of this systematic review is to identify the most significant experiences in the classroom that work on emotional intelligence through sports, as well as to clarify the instruments, strategies, and results of the studies to verify their effectiveness. The articles included in the review were published between 2018 and 2023 in the Web of Science, PubMed, and Scopus databases. Initially, 582 articles were identified, but after applying inclusion criteria, only 9 articles met the research objectives. It has been evidenced that it is important to integrate a systematic model of emotional skills in teacher training. Additionally, it has been discovered that emotional intelligence with its practical applications could be considered a strategy with a significant impact in the classroom.